Survey on the Occurrence of Viruses Infecting Cucurbits in Yogyakarta and Central Java - Budi Setiadi Daryono; Keiko T. Natsuaki (Jurnal Perlindungan Tanaman Indonesia, 2009)
Cucurbits are grown throughout the Java Island as dry season crops. Plants having mosaic, mottling, chlorosis and leaf distortion symptoms were frequently found in most of the cucurbit fields during the survey which conducted in Central Java including Sleman, Kulon Progo, and Klaten during July–September 2000 and 2001. Using double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA); Cucumber mosaic virus (CMV), Cucumber green mottle mosaic virus (CGMMV) and Kyuri green mottle mosaic virus (KGMMV) were found infecting cucurbits. CMV was widespread, infecting 48.9% of the samples tested followed by CGMMV (12.8%) and KGMMV (6.4%), while others samples (31.9%) were not tested, double infections were common with 8.5 % of the samples being infected with two viruses (CGMMV and KGMMV) and 34% with three viruses (CMV, CGMMV, and KGMMV). Severe mosaic and mottle symptoms were associated most often with single infection of CGMMV and KGMMV respectively. In addition, these are the first detections of CGMMV and KGMMV infecting cucurbit plants in Indonesia.